CRM Terhadap Loyalitas Pelanggan Berbasis Web - Putri, Sugini; Putra, Guntur Maha; Apridonal M, Yori (Institut Teknologi Garut, 2025)
E-commerce is the sale or purchase of services or goods between companies, households, individuals, governments, communities, or other private organizations, which are carried out through computers on network media. Customer Relationship Management is a corporate-level strategy that focuses on building and maintaining relationships with customers and in essence the company wants to build stronger bonds with customers that aim to maximize customer satisfaction. This research aims to develop a web-based CRM system to increase customer loyalty at Jaya Plastik store. The research method involves the use of use case diagrams for system design, implementation with Visual Studio Code, and MySQL database. Test results show that the system can increase product information transparency by 80% and retain 90% of active customers.